(untitled) (Advances in Applied Mathematics and Mechanics, 2024)
We present a numerical study that investigates the collision between a falling droplet and a sessile droplet on a superhydrophobic surface with various impact velocities, size ratios, and eccentric angles. After impact, the two droplets may merge into a bigger droplet. We use the OpenFOAM volume of the fluid method to monitor the droplet geometry, analyze the dynamic characteristics of the impact, determine the contact time of the merged droplet on the surface, and locate the contact line of the merged droplet. When a large droplet impacts a small droplet, increasing the eccentric angle decreases both the maximum spreading distance and the contact time for all impact velocities. Additionally, it reduces the number of broken small droplets that splash following fragmentation at high impact velocity. Droplets of equal size produce impacts that are nearly the same as those of a large droplet impacting a small droplet. The only difference occurs at the moment of droplet fragmentation. When a small droplet impacts a large droplet, increasing the eccentric angle by less than 10^° shortens the maximum spreading distance while only slightly increasing the contact time. In addition, droplet fragmentation is significantly reduced. The results provide insight into potential applications of droplet-solid interactions, which are valuable for engineering applications such as anti-icing and self-cleaning.